SOLAR PHOTOVOLTAIC DAN PENERAPANNYA MENJADI POWER BANK 10000 MAH - Goklas Miracle Siahaan; Lathifa Putri Afisna; Fransisco Dino Permadi; Oktavirnanda Oktavirnanda P (Program Studi Teknik Mesin Universitas Tarumanagara, 2022)
Consumers of mobile devices expect manufacturers to produce devices that will be an efficient source of electrical energy. The battery currently used in the smartphone allows the device to operate for several hours. PowerBank extends the operating time of the device without the need to charge it through a charger that is connected to the mains and the most important feature that determines the quality of a power bank is its capacity. This paper first analyzes the effect of the number of solar cells on the application of a 10000 mAh PowerBank. It has been shown in this study that the capacity of the 10000 mAh PowerBank can charge a series of 2, 4, and 8 solar cells. What has also been investigated is Then testing it for several types of mobile devices. The results show that using a 2, 4, and 8 solar cell circuit type can only charge handheld cell phones with a battery capacity of 2000 mAh.